1997
DOI: 10.1007/s004250050083
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the phloem lectin is developmentally linked to vascular differentiation in cucurbits

Abstract: The conducting elements of phloem in angiosperms are a complex of two cell types, sieve elements and companion cells, that form a single developmental and functional unit. During ontogeny of the sieve element/companion cell complex, specific proteins accumulate forming unique structures within sieve elements. Synthesis of these proteins coincides with vascular development and was studied in Cucurbita seedlings by following accumulation of the phloem lectin (PP2) and its mRNA by RNA blot analysis, enzyme-linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 26 publications
2
44
1
Order By: Relevance
“…Immunolocalization and in situ studies performed on wheat (13), cucurbit (20,29), rice (30), and tobacco, potato, and tomato (28) have established that, when expressed in vivo, the sieve tube proteins are confined to the companion cell-sieve tube complex. Thus, our present findings reveal two important facets associated with plasmodesmal function: (i) the plasmodesmal supramolecular structure does not constitute, in itself, the only discrimination site for cell-to-cell transport of macromolecules; and (ii) additional cell-specific factors (cytoplasmic or plasmodesmal) are likely involved in the regulation of macromolecular trafficking across specific cellular boundaries (e.g., the companion cell-sieve tube member interface) (11).…”
Section: Discussionmentioning
confidence: 99%
“…Immunolocalization and in situ studies performed on wheat (13), cucurbit (20,29), rice (30), and tobacco, potato, and tomato (28) have established that, when expressed in vivo, the sieve tube proteins are confined to the companion cell-sieve tube complex. Thus, our present findings reveal two important facets associated with plasmodesmal function: (i) the plasmodesmal supramolecular structure does not constitute, in itself, the only discrimination site for cell-to-cell transport of macromolecules; and (ii) additional cell-specific factors (cytoplasmic or plasmodesmal) are likely involved in the regulation of macromolecular trafficking across specific cellular boundaries (e.g., the companion cell-sieve tube member interface) (11).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PP2 has the capacity to interact with mesophyll plasmodesmata to increase the size exclusion limit and traffic cell-to-cell (Balachandran et al, 1997). This property reflects the apparent intercellular movement of PP2 within the sieve element-companion cell complex: PP2 mRNA was detected only in companion cells, although the protein accumulates in the sieve elements (Bostwick et al, 1992;Dannenhoffer et al, 1997). Additional experiments demonstrated that soluble, unpolymerized PP2 subunits translocate within sieve elements from source to sink tissues, and cycle between sieve elements and companion cells (Golecki et al, 1999).…”
mentioning
confidence: 99%
“…The phloem filament protein and phloem lectin have been localized immunocytochemically to both sieve elements and companion cells (Smith et al, 1987;Clark et al, 1997;Dannenhoffer et al, 1997). However, in situ hybridization experiments in hypocotyls of Cucurbita maxima seedlings established that PP1 and PP2 mRNAs accumulate only in companion cells in both immature and differentiated sieve element-companion cell complexes (Bostwick et al, 1992;Clark et al, 1997;Dannenhoffer et al, 1997). Thus, PP1 and PP2 apparently are synthesized in companion cells and subsequently transported into sieve elements via pore-plasmodesma contacts.…”
mentioning
confidence: 99%
“…Analysis of soluble phloem filaments present in phloem exudates of cucurbits indicated that PP1 monomers and PP2 dimers were covalently cross-linked via disulfide bonds, forming high molecular weight polymers Northcote, 1983a, 1983b). The phloem filament protein and phloem lectin have been localized immunocytochemically to both sieve elements and companion cells (Smith et al, 1987;Clark et al, 1997;Dannenhoffer et al, 1997). However, in situ hybridization experiments in hypocotyls of Cucurbita maxima seedlings established that PP1 and PP2 mRNAs accumulate only in companion cells in both immature and differentiated sieve element-companion cell complexes (Bostwick et al, 1992;Clark et al, 1997;Dannenhoffer et al, 1997).…”
mentioning
confidence: 99%